Archaeological age estimation based on obsidian hydration data for two southern Andean sources - Garvey, Raven (2016)
Obsidian is abundant in archaeological sites throughout Mendoza Province, Argentina but no obsidian hydration rates exist to date these assemblages. Direct dating of obsidian artifacts is particularly important in west-central Argentina because the surface record is extensive but well-defined time marker artifacts are lacking. The costs of non-optical hydration dating techniques currently preclude their regular use in the region, however. We present and evaluate 12 models for age estimation based on optical hydration rim measurements for the two most commonly used obsidian types in the region (Las Cargas and Laguna del Maule). Age estimation equations are derived for each source using observed hydration rim-radiocarbon date pairs, and parameterized by variables known to influence obsidian hydration in experimental settings. The equations advanced here are currently best at predicting the known ages of artifacts independently dated by radiocarbon, and can be cautiously used to estimate the ages of obsidian artifacts.